Optimizing fabrication processes for scalable production of flexible thermoelectric modules: A case study on self-powered IoT systems - Jakrit Gobpant; Bhanupol Klongratog; Chalermpol Rudradawong; Rachsak Sakdanuphab; Pichet Limsuwan; Aparporn Sakulkalavek (Results in Engineering)
This study explores the optimization of fabrication processes for flexible thermoelectric generators (FTEGs) to enhance their performance and scalability for industrial applications, with a focus on integrating them into self-powered Internet of Things (IoT) systems. The research investigates the impact of silicone layer thickness and applied fabrication pressures on the mechanical stability, energy harvesting efficiency, and power output of FTEGs. Results demonstrate that reducing the thermal conductivity of the silicone filler and optimizing the fabrication pressure significantly improves the performance of FTE modules. The optimized FTEGs, featuring a series-parallel configuration, achieve a power density of 5.2 mW/cm² under a temperature difference of 50 °C, surpassing prior benchmarks. The developed system efficiently harvests waste heat, charges a battery, and powers an IoT module for real-time monitoring of temperature, humidity, and carbon monoxide levels. These findings highlight the potential of FTEGs as a sustainable solution for energy harvesting and self-powered industrial monitoring applications.